2015
DOI: 10.1002/pbc.25833
|View full text |Cite
|
Sign up to set email alerts
|

The Sooner the Better? How Symptom Interval Correlates With Outcome in Children and Adolescents With Solid Tumors: Regression Tree Analysis of the Findings of a Prospective Study

Abstract: Background. The potential impact of diagnostic delays on patients' outcomes is a debated issue in pediatric oncology and discordant results have been published so far. We attempted to tackle this issue by analyzing a prospective series of 351 consecutive children and adolescents with solid malignancies using innovative statistical tools. Methods. To address the nonlinear complexity of the association between symptom interval and overall survival (OS), a regression tree algorithm was constructed with sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
3
46
0
2
Order By: Relevance
“…The potential impact of symptom interval on patient outcomes is still a debated issue in pediatric oncology, and published results have been discordant. While the intrinsic biological aggressiveness of a tumor clearly plays a major part in determining the symptom interval, some studies have reported that this time lag could negatively affect a patient's chances of survival, especially for certain kinds of tumor . A recent study by our group showed that the correlation between symptom interval and survival is a complex, heterogeneous phenomenon, but at least a subset of patients can benefit from an earlier diagnosis in survival terms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impact of symptom interval on patient outcomes is still a debated issue in pediatric oncology, and published results have been discordant. While the intrinsic biological aggressiveness of a tumor clearly plays a major part in determining the symptom interval, some studies have reported that this time lag could negatively affect a patient's chances of survival, especially for certain kinds of tumor . A recent study by our group showed that the correlation between symptom interval and survival is a complex, heterogeneous phenomenon, but at least a subset of patients can benefit from an earlier diagnosis in survival terms .…”
Section: Introductionmentioning
confidence: 99%
“…It can only come to light if patients report their symptoms to a physician . A common feature of cancer patients in this age group is regrettably the time elapsing before their disease is diagnosed, which is much longer than in the case of children . The potential impact of symptom interval on patient outcomes is still a debated issue in pediatric oncology, and published results have been discordant.…”
Section: Introductionmentioning
confidence: 99%
“…A long time to diagnosis for tumours is often associated with worse outcome, but this is not universal 16. In Ewing sarcoma, longer histories are not associated with worse outcome 13 17–19.…”
Section: Discussionmentioning
confidence: 99%
“…Research is another key issue for programs dedicated to AYA. Several studies on AYA have been conducted by the INT Youth Project staff (some already published, others ongoing) on matters such as psychosocial support needs, epidemiology, clinical outcomes, and basic science studies on tumor biology across the age spectrum …”
Section: Discussionmentioning
confidence: 99%